2022
DOI: 10.48550/arxiv.2202.00014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stellar Revival and Repeated Flares in Deeply Plunging Tidal Disruption Events

Chris Nixon,
Eric R. Coughlin

Abstract: Tidal disruption events with tidal radius r t and pericenter distance r p are characterized by the quantity β = r t /r p , and "deep encounters" have β ≫ 1. It has been assumed that there is a critical β ≡ β c ∼ 1 that differentiates between partial and full disruption: for β < β c a fraction of the star survives the tidal interaction with the black hole, while for β > β c the star is completely destroyed, and hence all deep encounters should be full. Here we show that this assumption is incorrect by providing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Successful captures are recorded when the distance between the two stars exceeds 50 a . All length scales can be measured relative to a , all timescales relative to a 3/2 / √ GM • , and all masses relative M • , but we restrict 1 Recent simulations have shown that β 1 can also result in the reformation of a stellar core following the initial stellar disruption (Nixon & Coughlin 2022), which could produce recurrent flares in more extreme versions of this type of Hills capture, i.e., with smaller black hole masses (to avoid direct capture) and larger β.…”
Section: Three-body Integrationsmentioning
confidence: 99%
“…Successful captures are recorded when the distance between the two stars exceeds 50 a . All length scales can be measured relative to a , all timescales relative to a 3/2 / √ GM • , and all masses relative M • , but we restrict 1 Recent simulations have shown that β 1 can also result in the reformation of a stellar core following the initial stellar disruption (Nixon & Coughlin 2022), which could produce recurrent flares in more extreme versions of this type of Hills capture, i.e., with smaller black hole masses (to avoid direct capture) and larger β.…”
Section: Three-body Integrationsmentioning
confidence: 99%